Atomistic simulations of ∑3 [110](111) grain boundary in diamond: Structure, stability, and properties. Issue 2 (22nd September 2022) - Pooja,; Pawar, Ravinder
Abstract: Grain boundaries play a pivotal role to influence the stability and mechanical properties of the diamond derived from chemical vapor deposition; therefore, the scrutiny of grain boundaries has aroused intensive research attention. In the present study, the structure, stability, mechanical, electronic properties, and concentration effect of the ∑3 [110](111) grain boundary in diamond has been investigated using density functional theory calculations. The grain boundary energy ( γ GB ), phonon dispersion relation, and charge density distribution clearly indicate that the ∑3 [110](111) grain boundary in diamond is stable. The elasticity and electronic properties of the diamond with the ∑3 [110](111) grain boundary closely resemble the pristine diamond. En route to determining the thermal stability of the grain boundary, molecular dynamics simulations using ReaxFF were performed at various temperatures. In addition, Young's modulus was calculated by applying an increasing 5.6% uniaxial strain along the z‐direction during the molecular dynamics simulations using ReaxFF. The ReaxFF simulations further demonstrate that the grain boundary is found to be thermally stable even at 1773.15 K. Abstract :